Activities of the Maghreb Unified Work Coordination Entities: "The Independent Direction as a Model" 1926-1954 CE. - tebani, yacine; dahache, saddek (Journal of Social Sciences and Humanities, 2024)
This study aims to show the role of the independent trend in adopting the unity of the common struggle of the three Maghreb countries, Tunisia, Algeria, and Al-Aqsa Maghreb. By finding formulas to employ the characteristics of the common identity in the Maghreb countries, activating the unified struggle against the French colonialism, and pushing the Maghreb elite to form streams and associations that aspire to structure common Maghreb action, and work to apply them in the context of confronting colonialism to bring the three national movements closer together, coordinate between their elites and leaders, and activate ways of common action that remained inconsistent at the country level within a unified collective frame work. These initiatives resulted in the establishment of the North African Star Party and the North African Students Association, which carry unified coordination ideas, based on basic principles derived from programs and charters that truly confirm their Maghare bian demands. The issue of the people’s independence was the main topic of the North African Star, during its founding conference in 1933, which focused in its articles on the unitary direction to realize the independence. The association’s conferences formed an axis for coordinating among North African students, especially in the third conference that held in Paris on December26th, 1933. This struggling march of the North African Star was embodied by the ideological and political principles and topics that it presented as a basis for common action as well as for reviving the idea of the Arab Maghreb